The survival of the city living and thriving in an age of isolation - Glaeser, Edward L. 1967-; Cutler, David M. 1965- (Basic books, 2021)
The city besieged -- Will globalization lead to permanent pandemic? -- Can Indian sewers make Indiana healthier? -- Can our bodies be more pandemic proof? -- Why did so much healthcare spending produce so little health? -- Do robots spread disease? -- What is the future of downtown? -- The battle for Boyle Heights and the closing of the metropolitan frontier -- Urbanization and its discontents -- A future with more hope than fear
Includes bibliographical references and index
Hier auch später erschienene Auflagen
Keywords: Urban economics; Urban health; Urban policy; Social aspects; City and town life; Social distancing; Epidemics; Stadtökonomie; Pandemie; COVID-19; Isolation -- Soziologie; Stadtleben; Kommunalpolitik